2017
DOI: 10.1002/uog.17418
|View full text |Cite
|
Sign up to set email alerts
|

Proposed clinical management of pregnancies after combined screening for pre‐eclampsia at 19–24 weeks' gestation

Abstract: Risk stratification of PE by the combined test at 19-24 weeks' gestation can identify, first, a group which constitutes < 1% of the total population and contains > 95% of those that will develop PE < 32 weeks and are in need of intensive monitoring at 24-31 weeks and, second, a group which constitutes < 20% of the total and contains > 90% of those that will develop PE at 32-35 weeks and are in need of reassessment at 32 weeks. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…We found that in pregnancies both with and without CHD that develop PE, impedance to flow in the uterine arteries is increased and this increase is particularly marked in those with preterm PE. Several previous studies have reported that, in pregnancies that develop PE, UtA-PI MoM is increased in the first, second and third trimesters and that the increase is related inversely to the gestational age at which delivery is undertaken for maternal and/or fetal indications 2,3,[9][10][11][17][18][19][20][21][22][23] . These Doppler ultrasound findings have been interpreted as supportive evidence for the results of histological studies that PE is associated with impairment of the physiological process of trophoblastic invasion of the maternal spiral arteries and their conversion from narrow muscular vessels to dilated non-muscular channels [24][25][26] .…”
Section: Main Findings Of Studymentioning
confidence: 97%
See 1 more Smart Citation
“…We found that in pregnancies both with and without CHD that develop PE, impedance to flow in the uterine arteries is increased and this increase is particularly marked in those with preterm PE. Several previous studies have reported that, in pregnancies that develop PE, UtA-PI MoM is increased in the first, second and third trimesters and that the increase is related inversely to the gestational age at which delivery is undertaken for maternal and/or fetal indications 2,3,[9][10][11][17][18][19][20][21][22][23] . These Doppler ultrasound findings have been interpreted as supportive evidence for the results of histological studies that PE is associated with impairment of the physiological process of trophoblastic invasion of the maternal spiral arteries and their conversion from narrow muscular vessels to dilated non-muscular channels [24][25][26] .…”
Section: Main Findings Of Studymentioning
confidence: 97%
“…In PE, particularly preterm PE, there is evidence from Doppler studies of impaired uteroplacental perfusion, reflected in increased uterine artery pulsatility index (UtA‐PI). The objective of this study is to investigate further the association between fetal CHD and maternal PE by examining second‐trimester UtA‐PI in pregnancies with and those without major CDH.…”
Section: Introductionmentioning
confidence: 99%
“…While aspirin commenced in the first trimester appears to reduce the development of PE, the same intervention seems ineffective when started after 20 weeks. Although it is too late to prevent the development of PE after second‐trimester prediction, the knowledge can still be useful in guiding follow‐up and management of a pregnancy at risk. However, the clinical impact of intensified follow‐up has yet to be proven.…”
Section: Management After Screeningmentioning
confidence: 99%
“…Fourth, the competing‐risks model has been successfully applied for assessment of risk for PE and stratification of pregnancy care by a combination of maternal factors and biomarkers in the first, second and third trimesters of pregnancy. In the first trimester, the competing‐risks approach utilizing maternal factors, MAP, UtA‐PI and PlGF was used to identify women at high risk of developing preterm PE; at a 10% screen‐positive rate, 90% of early‐PE cases and 75% of those with preterm PE were predicted in both a training dataset of 35 948 singleton pregnancies and in two independent, non‐intervention, multicenter studies involving 8775 and 16 451 singleton pregnancies, respectively.…”
mentioning
confidence: 99%
“…Consequently, appropriate evaluation and application of biomarkers in screening requires prior standardization by expressing the measured values as multiples of the median (MoM) [28][29][30][31] . In pregnancies that develop PE, MoM values of MAP, UtA-PI and sFlt-1 tend to be higher and PlGF tends to be lower than in normal pregnancies; the effect size increases with increasing severity of the disease, quantified by the gestational age at delivery 5-8 .Fourth, the competing-risks model has been successfully applied for assessment of risk for PE and stratification of pregnancy care by a combination of maternal factors and biomarkers in the first, second and third trimesters of pregnancy [32][33][34][35][36][37][38][39][40][41][42][43][44] . In the first trimester, the competing-risks approach utilizing maternal factors, MAP, UtA-PI and PlGF was used to identify women at high risk of developing preterm PE; at a 10% screen-positive rate, 90% of early-PE cases and 75% of those with preterm PE were predicted in both a training dataset of 35 948 singleton pregnancies and in two independent, non-intervention, multicenter studies involving 8775 and 16 451 singleton pregnancies, respectively 32,[45][46][47][48] .…”
mentioning
confidence: 99%